Mometasone furoate in the treatment of allergic rhinitis: a complex therapeutic effect - R. S. Fassakhov; D. I. Marapov (Медицинский совет, 2021)
The review examines the role of mometasone furoate (NSMF) intranasal spray (Nasonex) in the treatment of allergic rhinitis (AR). There is a wide prevalence of AR both among children and adults, its adverse effect on the quality of life of patients. It is emphasized that the main means of therapy for moderate and severe course in accordance with international and Russian recommendations for the diagnosis and treatment of AR are intranasal glucocorticosteroids (INGKS). The pharmacological features of the MF molecule that underlie its efficacy and safety, including the affinity, lipophilicity and viscosity of the drug, as well as low systemic bioavailability, are discussed in detail. The therapeutic effects of NSMF in the treatment of seasonal and perennial AR, its effect on nasal symptoms are discussed in detail. The beneficial effect of NSMF therapy on nasal congestion is emphasized separately. The beneficial effect of NSMF treatment on other clinical manifestations of AR, including ocular symptoms, effects on sleep, and olfactory function, has been noted. The safety issues of NSMF use are discussed in detail, including systemic effects, such as effects on adrenal function, eye, and growth retardation in children, and local adverse effects on the nasal mucosa; there is a high profile of local and systemic safety of long-term use of NSMF in the treatment of AR in both adults and children.